2020
DOI: 10.1038/s41409-020-01051-6
|View full text |Cite
|
Sign up to set email alerts
|

Better leukemia-free survival with allogeneic than with autologous HCT in AML patients with isolated trisomy 8: a study from the ALWP of the EBMT

Abstract: The indication for performing an allogeneic hematopoietic stem cell transplantation (allo-HCT) in patients with isolated trisomy 8 AML in first complete remission (CR) is still debated. Here, we compared outcomes of such patients given either allo-HCT or autologous (auto)-HCT. Inclusion criteria consisted of adult patients with de novo AML, isolated trisomy 8, first HCT between 2000 and 2018, CR1 at transplantation, and either auto-HCT or allo-HCT with a HLA-identical sibling donor (MSD) or a 10/10 HLA-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This assumption was recently confirmed by the EBMT that reported on 401 AML patients with an isolated trisomy 8 transplanted either with autologous or HLA-matched allogeneic HSCT in first remission. In this study, patients receiving allogeneic HSCT had a lower cumulative incidence of relapse (CIR), and-despite a higher non-relapse mortality (NRM)-longer RFS as well as a trend for longer overall survival (OS) [12]. Additionally, single center as well as registry-based analyzes indicated promising outcomes in larger cohorts of patients with a trisomy 8, further pointing to allogeneic HSCT as an effective consolidation treatment in these patients [10,13].…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…This assumption was recently confirmed by the EBMT that reported on 401 AML patients with an isolated trisomy 8 transplanted either with autologous or HLA-matched allogeneic HSCT in first remission. In this study, patients receiving allogeneic HSCT had a lower cumulative incidence of relapse (CIR), and-despite a higher non-relapse mortality (NRM)-longer RFS as well as a trend for longer overall survival (OS) [12]. Additionally, single center as well as registry-based analyzes indicated promising outcomes in larger cohorts of patients with a trisomy 8, further pointing to allogeneic HSCT as an effective consolidation treatment in these patients [10,13].…”
Section: Introductionmentioning
confidence: 73%
“…Regarding the optimal consolidation therapy in trisomy 8 patients, it has been suggested that chemotherapy alone may not have the ability to cure trisomy 8 AML [2,8], which was further underlined by a study by the EBMT showing more beneficial outcomes for trisomy 8 patients undergoing allogeneic HSCT compared to autologous HSCT consolidation [12]. Nevertheless, so far, no study compared outcomes of patients with or without a trisomy 8 after allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allogeneic hematopoietic stem cell transplantation (allo-HCT) has remained the best curative option for patients with poor or intermediate-risk AML in first complete remission (CR) as well as for AML patients in second CR (CR2) [1][2][3][4][5]. For patients who lack a fit HLA-identical sibling donor, transplantation with either an HLAmatched or HLA-mismatched unrelated donor (UD), HLAhaploidentical or umbilical cord blood (CB) donor has remained an adequate option.…”
Section: Introductionmentioning
confidence: 99%